2021
DOI: 10.1088/1755-1315/899/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Emission performance of major ship classes: An estimation based on a new set of emission factors and realistic activity profile data

Abstract: The maritime sector significantly contributes on the major environmental problems that humanity is being confronted with their consequences. The Greenhouse Gases (GHGs) emitted from the sector, which are responsible for the global phenomenon of climate change, are estimated in 2,89% of total anthropogenic GHGs. Ships are also an important source of local air-quality degradation in coastal areas by emitting major quantities of pollutants such as Nitrogen Oxides (NOx), Sulphur Oxides (SOx) and Particulate Matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Like the Belgian results, other studies have also indicated lower non-compliance levels for NO x compared to FSC. The most important finding, indicating higher non-compliance levels for Tier II and Tier III compared to Tier I, has also been confirmed in other studies [50,85,[88][89][90][91][92][93].…”
Section: Results Of Onboard Inspectionssupporting
confidence: 75%
“…Like the Belgian results, other studies have also indicated lower non-compliance levels for NO x compared to FSC. The most important finding, indicating higher non-compliance levels for Tier II and Tier III compared to Tier I, has also been confirmed in other studies [50,85,[88][89][90][91][92][93].…”
Section: Results Of Onboard Inspectionssupporting
confidence: 75%